The British Industrial Relations Bill – An Analysis - Whittingham, T.; Towers, B. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
In this paper, the authors attempt to analyse the government intention and to assess some of the possible implications of the proposed measures in the British government's industrial relations Bill passed on December 8, 1970.